2020
DOI: 10.1007/s11356-020-11729-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparative toxicity assessment of in situ burn residues to initial and dispersed heavy fuel oil using zebrafish embryos as test organisms

Abstract: In situ burning (ISB) is discussed to be one of the most suitable response strategies to combat oil spills in extreme conditions. After burning, a highly viscous and sticky residue is left and may over time pose a risk of exposing aquatic biota to toxic oil compounds. Scientific information about the impact of burn residues on the environment is scarce. In this context, a comprehensive ISB field experiment with approx. 1000L IFO 180 was conducted in a fjord in Greenland. The present study investigated the toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 92 publications
(145 reference statements)
1
4
0
Order By: Relevance
“…The PAH concentrations were 0.185 mg/L in WAF of initial oil, and 0.052 mg/L in WAF of burned oil which for the same 18 PAHs is in the same range as in our study which was 0.165 mg/L and 0.030 mg/l, respectively. In line with our results Johann et al [ 11 ] observed higher acute mortality for the fresh oil WAF than for the burnt residue WAF. However, based on the sublethal effects they concluded that there were no overt differences in the acute toxicity of the WAFs of IFO180 and burned IFO180 to zebrafish embryos.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The PAH concentrations were 0.185 mg/L in WAF of initial oil, and 0.052 mg/L in WAF of burned oil which for the same 18 PAHs is in the same range as in our study which was 0.165 mg/L and 0.030 mg/l, respectively. In line with our results Johann et al [ 11 ] observed higher acute mortality for the fresh oil WAF than for the burnt residue WAF. However, based on the sublethal effects they concluded that there were no overt differences in the acute toxicity of the WAFs of IFO180 and burned IFO180 to zebrafish embryos.…”
Section: Resultssupporting
confidence: 93%
“…In a recent study, Johann et al [ 11 ] prepared LE-WAFs with IFO180 and ISB residue of IFO180 for exposure experiments using zebrafish in a fish acute embryo toxicity test (120 h post fertilization). The WAF concentrations were quantified by 18 unsubstituted PAHs, but neither TPH nor volatiles were analysed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fish embryo acute toxicity test was applied as a limit test with fertilized eggs of the zebrafish ( Danio rerio) , based on the DIN guideline and the OECD guideline 236 (DIN EN ISO, 2008 ; OECD, 2013a ; Shuliakevich et al, 2022b ). As described in Johann et al ( 2021 ), the experiments were terminated shortly before 120-h post-fertilization (hpf). According to the Directive 2010/63/EU (European Union, 2010 ), testing zebrafish embryos and larvae before 120 hpf does not require animal ethics test approval.…”
Section: Methodsmentioning
confidence: 99%
“…The species in local vicinity face the death fate with in short duration of the spill accidents 17–19 . Deformities in the embryo of many species of fish 20 and shift in the community composition of species 13 are the reported long term effects 21 . Some of the cleanup methods also pollute the local environment 22 and put serious risk on the survival of the surrounding species 23 …”
Section: Introductionmentioning
confidence: 99%